Penggunaan Metode Cerita dalam Meningkatkan Minat Belajar PAI pada Siswa di MI Ummul Quro - Maskanah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Student interest in Islamic Religious Education (PAI) at the elementary school level tends to decline, especially when the learning process is delivered monotonously and lacks context. At MI Ummul Quro, it was found that some students showed a lack of interest in Islamic Religious Education (PAI) lessons, despite the teacher's limited use of storytelling methods. The focus of this study is the use of storytelling methods to increase students' interest in learning PAI at MI Ummul Quro. This study aims to describe the use of storytelling methods in increasing interest in learning PAI in students at MI Ummul Quro, including aspects such as interest, participation, understanding, internal motivation, and the ability to apply religious values in everyday life. The method used was descriptive qualitative research with a case study approach. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the interactive model of Miles and Huberman. The results showed that the use of Islamic storytelling methods delivered in an engaging and interactive manner significantly increased students' interest in learning. Students became more enthusiastic, more active in learning activities, better understood the material, and demonstrated increased internal motivation and religious behavior.